Dose–response to 3 months of quercetin-containing supplements on metabolite and quercetin conjugate profile in adults - Cialdella-Kam, Lynn; Nieman, David C.; Sha, Wei; Meaney, Mary Pat; Knab, Amy M.; Shanely, R. Andrew (British journal of nutrition, 2013)
Quercetin, a flavonol in fruits and vegetables, has been demonstrated to have antioxidant, anti-inflammatory and immunomodulating influences. The purpose of the present study was to determine if quercetin, vitamin C and niacin supplements (Q-500 = 500 mg/d of quercetin, 125 mg/d of vitamin C and 5 mg/d of niacin; Q-1000 = 1000 mg/d of quercetin, 250 mg/d of vitamin C and 10 mg/d of niacin) would alter small-molecule metabolite profiles and serum quercetin conjugate levels in adults. Healthy adults (fifty-eight women and forty-two men; aged 40–83 years) were assigned using a randomised double-blinded placebo-controlled trial to one of three supplement groups (Q-1000, Q-500 or placebo). Overnight fasted blood samples were collected at 0, 1 and 3 months. Quercetin conjugate concentrations were measured using ultra-performance liquid chromatography (UPLC)-MS/MS, and metabolite profiles were measured using two MS platforms (UPLC-quadrupole time-of-flight MS (TOFMS) and GC-TOFMS). Statistical procedures included partial least square discriminant analysis (PLS-DA) and linear mixed model analysis with repeated measures. After accounting for age, sex and BMI, quercetin supplementation was associated with significant shifts in 163 metabolites/quercetin conjugates (false discovery rate, P< 0·05). The top five metabolite shifts were an increase in serum guaiacol, 2-oxo-4-methylthiobutanoic acid, allocystathionine and two bile acids. Inflammatory and oxidative stress metabolites were not affected. PLS-DA revealed a clear separation only between the 1000 mg/d and placebo groups (Q2Y= 0·763). The quercetin conjugate, isorhamnetin-3-glucuronide, had the highest concentration at 3 months followed by quercetin-3-glucuronide, quercetin-3-sulphate and quercetin diglucuronide. In human subjects, long-term quercetin supplementation exerts disparate and wide-ranging metabolic effects and changes in quercetin conjugate concentrations. Metabolic shifts were apparent at the 1000 mg/d dose; further research is required to understand the health implications of these shifts.